EDUKASI PENCEGAHAN DAN PENGENDALIAN DIABETES MELITUS PADA KADER POSYANDU DI RT. 18 RW. 05 KELURAHAN LANJAS KECAMATAN TEWEH TENGAH - Jeany Zuliana; Septian Emma Dwi Jatmika (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Health problems that occur in RT. 18 RW. 05 Lanjas Village are Diabetes Melitus. Lack of knowledge about types, symptoms, risk factors, and lack of awareness of healthy lifestyles such as enthusiastic intake of sweet foods, smoking, sedentary lifestyles, and extraordinary glycemic control are diabetes in RT. 18 RW. 05 Lanjas Village. Health promotion as a preventative and control measure for executives RT. 18, Kelurahan Lanjas is conducted through education about diabetes, using educational media in the form of flyers. The purpose of counseling is to increase knowledge about Diabetes Melitus and increase public awareness of RT. 18, Lanjas Village to implement a clean and healthy lifestyle. The method used in advisory activities consists of three phases, namely the preparation, implementation and evaluation. The results of the counseling activities were an increase in participants' knowledge before being given Diabetes Melitus counseling, the results of the pre-test of participants in the low category of 20% and the high category of 10%, while after being given counseling the post-test results of all participants were in the high category of 100 %. It is hoped that executives and related health centers will be able to carry out diabetes counseling activities on a periodically basis to prevent and manage diabetes.